(untitled) (Global Journal of Medical Research, 2020)
The review was aimed at understanding the immune dysregulation by the novel virus, COVID-19. The review also highlighted the major findings that have been published in the previous studies through secondary research about the mechanism of immune dysregulation, transmission and progression of the virus across the globe. Adults above the age of 60 years and with co-morbidities such as cardiac and renal dysfunction, hypertension and diabetes are predisposed to greater risk of COVID-19 infection. The virus impairs the physiological, psychological and metabolic functioning of the patient. The paper gained an insight into the need for immunization priority for the Indian population and recommendations for the effective policy making in vaccine development and distribution.